Extracellular ATP-Induced Alterations in Extracellular H+ Fluxes From Cultured Cortical and Hippocampal Astrocytes - Choi, Ji-in Vivien; Tchernookova, Boriana K.; Kumar, Wasan; Kiedrowski, Lech; Goeke, Calla; Guizzetti, Marina; Larson, John; Kreitzer, Matthew A.; Malchow, Robert Paul (Frontiers in Cellular Neuroscience, 2021)
Small alterations in the level of extracellular H+ can profoundly alter neuronal activity throughout the nervous system. In this study, self-referencing H+-selective microelectrodes were used to examine extracellular H+ fluxes from individual astrocytes. Activation of astrocytes cultured from mouse hippocampus and rat cortex with extracellular ATP produced a pronounced increase in extracellular H+ flux. The ATP-elicited increase in H+ flux appeared to be independent of bicarbonate transport, as ATP increased H+ flux regardless of whether the primary extracellular pH buffer was 26 mM bicarbonate or 1 mM HEPES, and persisted when atmospheric levels of CO2 were replaced by oxygen. Adenosine failed to elicit any change in extracellular H+ fluxes, and ATP-mediated increases in H+ flux were inhibited by the P2 inhibitors suramin and PPADS suggesting direct activation of ATP receptors. Extracellular ATP also induced an intracellular rise in calcium in cultured astrocytes cells, and ATP-induced rises in both calcium and H+ efflux were significantly attenuated when calcium re-loading into the endoplasmic reticulum was inhibited by thapsigargin. Replacement of extracellular sodium with choline did not significantly reduce the size of the ATP-induced increases in H+ flux, and the increases in H+ flux were not significantly affected by addition of EIPA, suggesting little involvement of Na/H+ transporters in ATP-elicited increases in H+ flux. Given the high sensitivity of voltage-sensitive calcium channels on neurons to small changes in levels of free H+, we hypothesize that the ATP-mediated extrusion of H+ flux from astrocytes may play a key role in regulating signaling at synapses within the nervous system.